The Role of Application Programming Interface in Transforming Restaurant Delivery Operations - Cicilia Sriliasta Bangun; Solahudin Solahudin; Asep Sutarman; Sipho Dlamini (Startupreneur Business Digital (SABDA Journal), 2026)
The rapid growth of online food delivery services has transformed the restaurant industry, requiring efficient and scalable solutions to meet increasing customer demands. However, traditional restaurant management systems often struggle with integration challenges, operational inefficiencies, and customer dissatisfaction due to delays and miscommunication. This study aims to analyze the role of Application Programming Interfaces (API) in optimizing restaurant delivery operations by enhancing order management, inventory tracking, and real-time customer interactions. Using a mixed-method approach, we conducted case studies on multiple restaurant platforms and surveyed industry professionals to assess the effectiveness of API integration. The findings reveal that API-driven systems significantly improve delivery accuracy, reduce processing time, and enhance customer experience by automating order workflows and enabling seamless third-party service connections. The results indicate that restaurants leveraging API can achieve a higher level of efficiency and scalability, minimizing operational bottlenecks while maintaining service quality. This research concludes that API play a crucial role in transforming restaurant delivery operations, providing a competitive advantage in the evolving digital marketplace. Future studies should explore the impact of emerging technologies such as AIpowered API and blockchain integration for further optimization.